2021
DOI: 10.35308/akbis.v5i2.3946
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Independensi, Pengalaman, Skeptisme Profesional Auditor Dan Kompetensi Terhadap Kemampuan Auditor Dalam Mendeteksi Kecurangan (Studi Pada Inspektorat Aceh)

Abstract: Tujuan dari penelitian ini adalah untuk menguji pengaruh independensi, pengalaman, skeptisisme profesional auditor dan kompetensi terhadap kemampuan auditor dalam mendeteksi kecurangan. Populasi dalam penelitian ini adalah seluruh auditor yang bekerja di Inspektorat Aceh. Teknik pengambilan sampel menggunakan non probability sampling dengan metode sensus. Pengumpulan data dalam penelitian ini menggunakan kuesioner yang dibagikan kepada 48 auditor. Metode analisis data yang digunakan adalah regresi linier berga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Independence is one of the factors that motivates auditors to carry out audits objectively and free from the influence of other parties, making it easier for auditors to assess signs of fraud. The results of this research are in line and consistent with previous research conducted by (Hamilah, 2019) , (Muntasir & Maryasih, 2021) and (Putra et al, 2021) which states that independence has a positive effect on the auditor's ability to detect fraud . (Pramawastika & Primasari, 2023) revealed that the more independent an auditor is, the more capable he will be of detecting fraud.…”
Section: Independence (X2) Has a Positive Effect On The Auditor's Abi...supporting
confidence: 91%
“…Independence is one of the factors that motivates auditors to carry out audits objectively and free from the influence of other parties, making it easier for auditors to assess signs of fraud. The results of this research are in line and consistent with previous research conducted by (Hamilah, 2019) , (Muntasir & Maryasih, 2021) and (Putra et al, 2021) which states that independence has a positive effect on the auditor's ability to detect fraud . (Pramawastika & Primasari, 2023) revealed that the more independent an auditor is, the more capable he will be of detecting fraud.…”
Section: Independence (X2) Has a Positive Effect On The Auditor's Abi...supporting
confidence: 91%